2014
DOI: 10.1186/1477-7819-12-124
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin silencing inhibits proliferation and reduces invasion in human laryngeal squamous carcinoma cells

Abstract: BackgroundClusterin is, in its major form, a secreted heterodimeric disulfide-linked glycoprotein (sCLU), which plays important roles in cell survival and death. In laryngeal squamous cell carcinomas (LSCC), sCLU is up-regulated and its expression is related to the invasiveness of these tumors. The purpose of this study was to explore the inhibiting role of sCLU gene silence in the invasive ability and growth of Hep-2 human laryngeal squamous carcinoma cells (Hep-2) by transfection of short hairpin RNA express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…The protective role of hyperthermia‐induced CLU in HaCaT cells was supported by the findings that cell viability was significantly decreased in CLU‐KO group as compared with that of wild‐type and NC groups. Similar results were reported by Fu and Wang et al 29,30 . who found that there was a significant decrease in proliferation of ovarian cancer cells and laryngeal squamous carcinoma cells following CLU silencing with shRNA or siRNA.…”
Section: Discussionsupporting
confidence: 90%
“…The protective role of hyperthermia‐induced CLU in HaCaT cells was supported by the findings that cell viability was significantly decreased in CLU‐KO group as compared with that of wild‐type and NC groups. Similar results were reported by Fu and Wang et al 29,30 . who found that there was a significant decrease in proliferation of ovarian cancer cells and laryngeal squamous carcinoma cells following CLU silencing with shRNA or siRNA.…”
Section: Discussionsupporting
confidence: 90%
“…As previously reported by our group and others, down‐regulation of CLU reduces cell proliferation (Trougakos et al , ; Niu et al , ; Wang et al , ). In PC3 cells, down‐regulation of CLU results in decreased cell proliferation (Fig A) and a 40% mean increase in population of G2/M cells (Fig B).…”
Section: Resultssupporting
confidence: 84%
“…Clusterin (CLU), a multifunctional glycoprotein also known as apolipoprotein J, plays a role in several cellular processes including apoptosis, proliferation, and clearance of misfolded proteins (Kim and Choi, 2011,Wang, et al, 2014,Wyatt, et al, 2011). CLU is ubiquitous and is highly expressed in the brain by astrocytes (de Silva, et al, 1990).…”
Section: Introductionmentioning
confidence: 99%